The impact of macro economy toward profitability of Islamic bank - Yunice Karina Tumewang; Rindang Nuri Isnaini; Jannatul Liutammima Musta’in (Faculty of Business & Economics, Universitas Islam Indonesia, 2019)
Purpose: The aim of this study was to examine the impact of macro economy variables such as inflation, interest rate, and exchange rate toward the profitability of Islamic bank.Methodology: The research used quantitative approach through purposive sampling by using secondary data in the form of monthly time series from January 2015 to December 2012.Findings: The result shows that the inflation rate does not affect the bank income. The interest rate influences bank management in determining the level of margins and profit sharing so that partners continue to use Islamic bank products. In addition, the exchange rate does not have significant effect on the income of Islamic banks.Originality: As far as we are concerned, there are only few publications examining the effect of macro economy variable toward profitability of Islamic bank, particularly in the largest Muslim country during the period of December 2012-January 2015.